Convergent recruitment of new pollinators is triggered by independent hybridization events in Narcissus. Issue 2 (6th January 2016) - Marques, Isabel; Jürgens, Andreas; Aguilar, Javier Fuertes; Feliner, Gonzalo Nieto
Summary: Hybridization can generate new species if some degree of isolation prevents gene flow between the hybrids and their progenitors. The recruitment of novel pollinators by hybrids has been hypothesized to be one way in which such reproductive isolation can be achieved. We tested whether pollinators contributed to isolation between two natural Narcissus hybrids and their progenitors using pollination experiments, observations, plus morphological and floral‐volatile measurements. These hybrids share the same maternal but different paternal progenitors. We found that only the hybrids were visited by and pollinated by ants. The two hybrids exceeded their progenitors in floral‐tube aperture size and nectar production. The emission of floral volatiles by hybrid plants was not only equal to or higher than the progenitor species, but also contained some new compounds not produced by the progenitors. The recruitment of ants as novel pollinators in the hybrids involved the combination of increased nectar secretion and the production of novel floral scent compounds. A breakdown of chemical defence against ants may also be involved. This study provides support for the hypothesis that the recruitment of novel pollinators can contribute to reproductive isolation between hybrids and their progenitors.